The human side of digital business transformation - Lardi, Kamales (John Wiley & Sons, 2023)
"This book will be a guide for business leaders not only on how to implement digital business transformation, but also how to manage the internal (employees) and external (customer) stakeholders involved in the transformation. Key features include A proven digital business transformation framework to implement successful strategies Digital maturity and readiness assessment with an online tool for readers to try Best practices and key learnings to drive the human side of transformation Real case examples from companies that have implemented transformation and culture change initiatives Personal stories from recognized business leaders that include lessons learnt and success factors The checklist for digital business transformation"--